TRANSFORMATION OF BEHAVIORAL DETERMINANTS OF SCHOOL-AGE CHILDREN’S HEALTH UNDER MARTIAL LAW - Hozak, S.V.; Yelizarova, O.T.; Stankevych, T.V.; Kalynychenko, I.O.; Parats, A.M. (Environment & Health, 2026)
AIM. To assess dynamics of behavioral strategies and schooling characteristics among schoolage children to inform targeted interventions during prolonged military crisis. MATERIALS AND METHODS. Between April and June of 2022-2025 an online parental survey was conducted (n=10011; 5095 boys, 4916 girls) using the QRAPH questionnaire; sample recruited via snowballing and education departments; respondents whose children were ill, in rehabilitation or participating in competitions were excluded. Analyzed indicators included light physical activity (LPA), moderatetovigorous physical activity (MVPA), total physical activity (PAtotal), sedentary behaviour (SB), sleep duration, walking time, school lessons and homework; data processed in Excel, statistical analysis with STATISTICA 8.0. RESULTS. Total physical activity increased progressively from 2022 to 2025 across age and sex groups; mean PAtotal 1318 min/week (3.1 h/day) for both sexes; share of children achieving MVPA≥60 min/day rose from 21.6% (2022) to 42.1% (2025). Sleep averaged 8.2–8.3 hours/day with no sex differences. Schooling mode shifted from predominantly remote in 2022 to predominantly facetoface in 2025, which aligned with increased PA and reduced homework time under inperson schooling. CONCLUSIONS. Behavioral determinants among schoolchildren during wartime are adaptable – showing a shift from passive strategies early in the war toward more active behaviours by 2024–2025. Findings support age and sexspecific health promotion programs.